2020
DOI: 10.1186/s13104-020-05031-3
|View full text |Cite
|
Sign up to set email alerts
|

AST/ALT ratio predicts the functional severity of chronic heart failure with reduced left ventricular ejection fraction

Abstract: Objective: Despite previous research that focused on liver transaminases as predictors of cardiovascular disease, there has been limited research evaluating the predictive value of AST/ALT ratio in patients with heart failure. We aimed to investigate AST/ALT ratio as an indicator of the functional severity in chronic heart failure with reduced left ventricular ejection fraction. Results:Overall, 105 patients previously diagnosed with HFrEF from Buraidah-Al Qassim province, Saudi Arabia were included in this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 31 publications
1
41
0
5
Order By: Relevance
“…Presious studies have shown that AST/ALT was associated with cardiovascular disease. For instance, Mohammed Ewid et alconducted a study which evaluated the functional severity of chronic heart failure with reduced left ventricular ejection(HFrEF) , found that 0.9 was the best predictive cut-off value of the AST / ALT ratio [16] . At the same time,a study demonstrated that the best cut-off value in predicting the cardiometabolic risk in the AST / ALT ratio was 1 [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Presious studies have shown that AST/ALT was associated with cardiovascular disease. For instance, Mohammed Ewid et alconducted a study which evaluated the functional severity of chronic heart failure with reduced left ventricular ejection(HFrEF) , found that 0.9 was the best predictive cut-off value of the AST / ALT ratio [16] . At the same time,a study demonstrated that the best cut-off value in predicting the cardiometabolic risk in the AST / ALT ratio was 1 [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that AST/ALT ratio was associated with cardiovascular disease. For instance, Mohammed Ewid et alconducted a study which evaluated the association between AST/ALT ratio and functional severity of chronic heart failure with reduced left ventricular ejection (HFREF), suggested that AST/ALT ratio of 0.9 was the best cut-off value to forecast left ventricular function status [15] . At the same time, a study demonstrated that the best cut-off value of the AST / ALT ratio in predicting the cardiometabolism risk in was 1 [16] .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Mohammed Ewid et alconducted a study which evaluated the association between AST/ALT ratio and functional severity of chronic heart failure with reduced left ventricular ejection (HFREF) , suggested that AST/ALT ratio of 0.9 was the best cut-off value to forecast left ventricular function status [21] . At the same time, a study demonstrated that the best cut-off value of the AST / ALT ratio in predicting the cardiometabolism risk in was 1 [21,22] . In addition Gao F et al analyzed the relationship between AST / ALT ratio and poor outcomes prognosis in patients with acute ischemic stroke [23] .…”
Section: Discussionmentioning
confidence: 99%